Assessing Corporate Sustainability through an Islamic Ethical Responsibility Framework: Evidence from Multinational Food and Beverage Firms in Indonesia - Sabbar Dahham Sabbar; Sitti Nurjannah; Subehan Khalik; Mursalim Nohong; Arifuddin Mannan; Omer Mohamed Taha Alkanan; Zainab Mardhi Kazim (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
: Corporate sustainability has become a central paradigm in contemporary business governance. However, the prevailing Environmental, Social, and Governance (ESG) frameworks remain limited in accommodating context-specific legal and ethical traditions, particularly those derived from Islamic jurisprudence. This study addresses this gap by developing the Islamic Ethical Responsibility Framework (IERF), an analytical framework that operationalizes Islamic legal reasoning into a set of measurable criteria for assessing corporate sustainability. Employing a qualitative doctrinal legal research design combined with structured documentary analysis, the study examines the sustainability reports of multinational food and beverage companies listed on the Indonesia Stock Exchange (IDX). The IERF evaluates corporate sustainability through four analytical dimensions: Ethical Responsibility, Sustainable Products, Environmental Strategies, and Business Sustainability. The findings reveal substantial variation in the sustainability performance of the companies examined. Ethical Responsibility emerged as the most comprehensively disclosed dimension, reflecting strong corporate commitments to governance, transparency, and stakeholder accountability. In contrast, Environmental Strategies exhibited a comparatively lower level of disclosure, indicating that the integration of environmental stewardship into corporate sustainability practices remains a significant challenge. These findings further suggest that conventional ESG-oriented assessment frameworks do not fully capture the broader legal and ethical responsibilities emphasized in Islamic jurisprudence. Theoretically, this study contributes by operationalizing Islamic legal reasoning into a structured framework for corporate sustainability assessment and demonstrating how the principles of maqāṣid al-sharīʿah, amānah, ʿadl, khilāfah, and maṣlaḥah can serve as normative foundations for contemporary corporate governance. By bridging Islamic jurisprudence with the global sustainability discourse, the Islamic Ethical Responsibility Framework (IERF) offers a contextually grounded model for evaluating corporate sustainability within the broader framework of Contextualized Islamic Law